Coagulation Changes during Termination of Pregnancy by Prostaglandins and by Vacuum Aspiration. Issue 5844 (6th January 1973) - Badraoui, M. H. H.; Bonnar, John; Hillier, Keith; Embrey, M. P.
Abstract : Serial studies on coagulation factors were performed on 12 patients having termination of mid-trimester pregnancy by extra-amniotic prostaglandin F2 α and 11 patients terminated by vacuum aspiration during the first trimester. A significant change in the activity of factors V, VII and X, VIII, and X, and a decrease of the prothrombin time and platelet count were found with prostaglandin termination but no such changes occurred during vacuum aspiration. These findings suggest that the coagulation system is activated during induction of mid-trimester abortion with extra-amniotic prostaglandin F2 α. This is probably related to the physiological changes in the coagulation mechanism which occur by the second trimester of pregnancy. Termination of pregnancy in the mid-trimester may, however, be expected to give rise to defective blood coagulation and thromboembolic complications.